2007
DOI: 10.1348/000712606x147790
|View full text |Cite
|
Sign up to set email alerts
|

Children's recognition of time in the causes and cures of physical and emotional reactions to illnesses and injuries

Abstract: The present set of studies examined children's and college students' recognition of the role of time in the manifestation of causes and cures for illnesses and injuries. In Study 1, participants ranging from 4-year-olds through college students were presented with biological, moral, psychological, and irrelevant causes for illness symptoms and were asked how much time elapsed between the cause and the symptom. They were also asked if medicine would make the person feel better and if so how much time elapsed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Curability was investigated with ‘yes’ and ‘no’ cards. With respect to timeline, previous work has shown that even young children (4‐ and 5‐year‐olds) recognize that there is a temporal gap before recovery from an illness (Raman & Gelman, 2007). Timeline cards for the present study were generated directly from children's responses in relation to timeline in the focus group study.…”
Section: Methodsmentioning
confidence: 99%
“…Curability was investigated with ‘yes’ and ‘no’ cards. With respect to timeline, previous work has shown that even young children (4‐ and 5‐year‐olds) recognize that there is a temporal gap before recovery from an illness (Raman & Gelman, 2007). Timeline cards for the present study were generated directly from children's responses in relation to timeline in the focus group study.…”
Section: Methodsmentioning
confidence: 99%
“…This is especially true in the case of AIDS, where the incubation period can be extraordinarily long. Given that children lack a detailed understanding of the biological mechanisms that underlie illness (Au, Romo, & Dewitt, 1999), and have difficulty understanding the incubation period of illness (Kalish, 1996; Raman & Gelman, 2007), they may have difficulty appreciating their hidden nature. To address this issue, participants were provided with vignettes designed to assess the understanding that a person can be sick and not show symptoms, and that a person can be infected with an illness and not know it.…”
Section: Studymentioning
confidence: 99%
“…Since, injuries are non‐contagious, these items were included in all the studies to determine if participants apply intentionality only to contagious illnesses or if they think intentionality can affect the incursion of injuries. The exemplars of illnesses and injuries used in the following studies have all been successfully used with preschool populations in previous research (Kalish, 1995; Raman & Gelman, 2007, 2008). As stated earlier, two outcomes are possible: (1) participants might reason that the intentionality of the recipient will affect the probability of contracting an illness; or (2) participants might judge that the recipient's intentions are irrelevant in the manifestation of illness.…”
Section: Studymentioning
confidence: 99%
“…This conclusion is based on studies that have reported that preschoolers actively reject non‐biological causes (such as moral causes) as potential factors for the origins of illnesses (Kalish, 1996; Siegal, 1988; Springer & Belk, 1994; Springer & Ruckel, 1992; Raman & Winer, 2004). Moreover, preschoolers also make the distinction that illnesses but not injuries are transmittable (Raman & Gelman, 2007, 2008; Williams & Binnie, 2002). Thus, the overall consensus in the field (at least when examining the impact of social or moral factors) is that children entertain an autonomous theory of biology by the end of the preschool years (Wellman & Gelman, 1992).…”
mentioning
confidence: 99%